An Unusual Histology for a Lung Nodule: A Case Report of Primary Pulmonary Paraganglioma - Mazzucco, Alessandra; Poirè, Eleonora; Leporati, Andrea; Chiari, Matteo; Moneghini, Laura; Ghilardi, Giorgio; Baisi, Alessandro (Frontiers in Surgery, 2021)
Introduction: Primary pulmonary paraganglioma is a rare tumor with few cases reported in literature and unspecific clinical presentation. Case Presentation: A 49-year-old woman presented to our department with an incidental finding of a pulmonary mass at chest X-ray and no associated clinical symptom. The CT scan and the FDG-PET showed mild uptake of contrast, but a definitive diagnosis was only possible after surgery through histopathological examination. Conclusion: Paragangliomas originating in the pulmonary tissue are generally non-functioning masses discovered incidentally in otherwise asymptomatic patients. Surgery appears to be the best treatment option, with only radiologic follow-up necessary afterwards.